Impact of exposure to cold and cold-osmotic stresses on virulence-associated characteristics of Listeria monocytogenes strains. (May 2020) - Alves, Ângela; Magalhães, Rui; Brandão, Teresa R.S.; Pimentel, Lígia; Rodríguez-Alcalá, Luis M.; Teixeira, Paula; Ferreira, Vânia
Abstract: The objective of this work was to investigate the effect of stress conditions frequently encountered in food-associated environments on virulence-associated characteristics of eight strains of Listeria monocytogenes . Strains were grown at low (11 °C, cold stress) and optimal (37 °C) temperatures and in high NaCl concentrations (6% NaCl, 11 °C; cold-osmotic stress) and tested for their ability to invade the human intestinal epithelial Caco-2 cells. Results demonstrate that the correlation between exposure to cold stress and increased invasion phenotype is strain-dependent as strains investigated exhibited different behaviours, i.e. exposure to cold stress conditions resulted in a significant increase of invasion levels in five out of the eight strains tested, when compared to growth under optimal conditions. On the other hand, when these cold-adapted cells were subsequently submitted to high salt concentrations and low temperature, their enhanced ability to invade Caco-2 was lost. Surprisingly, saturated fatty acids (SFA) and branched chain fatty acids (BCFA) decreased when L. monocytogenes were exposed to stress conditions as opposed to what has been observed in other studies, therefore highlighting that further studies will need to deepen in the understanding of the lipid metabolism of these strains. The effect of stress conditions on the survival of three selected L. monocytogenes strains through an in vitro gastrointestinal (GI) tract digestion model was further investigated. The exposure to cold-osmotic stress increased the survival of one strain through the GI tract. Highlights: Stress conditions on virulence traits of L. monocytogenes investigated. Growth at 11 °C resulted in a significant increase of invasiveness in five strains. Correlation between cold stress and increased invasiveness was strain-dependent. Subsequent exposure to cold-osmotic stress resulted in reduced invasiveness. SFA and BCFA decreased when L. monocytogenes were exposed to stress conditions.